Local Taxation and Development Finance in the DRC: A Comment on Balán et al. (2022) - Sossou Adjisse; Moussa P. Blimpo; Paul Casta\~neda Dower (Institute for Replication (I4R), 2024)
Balán et al. (2022) evaluate the impact of "local elites" involvement in local tax collection in a large city in the Democratic Republic of Congo. Using a randomized controlled trial to vary the identities of tax collectors, they find that local elites' involvement raises tax compliance and total revenue by 50 and 44 percent, respectively. The paper argues that the primary mechanism behind the results is better targeting made possible by local elites' superior information about property holders' willingness and ability to pay. In this replication comment, we first reproduce the paper's main results. Then, we assess the robustness of the results by (1) employing randomization inference for statistical tests; (2) controlling for baseline characteristics that are not balanced; and (3) using an alternative method to examine the claims supporting the preferred mechanism of better targeting. We find robust estimates in (1). However, the results are less robust both in terms of statistical significance and magnitude for (2) and (3). We conclude that the average treatment effect is robust, while the main claim about mechanisms, the information channel, is less robust to alternative estimation approaches. We contextualize and discuss the significance of these results, including the negligible revenue potential even under full compliance.
Keywords: 330